Ketamine anaesthesia for medical procedures in children. Issue 1 (January 1976) - Elliott, E; Hanid, T K; Arthur, L J; Kay, B
Abstract : Ketamine hydrochloride 2 mg/kg, together with atropine 0.2 mg, has been given intravenously on 100 occasions on a general paediatric ward. No serious side effects occurred. Dreams followed in 4 children but did not reduce acceptability of the drug. In our hands it has greatly reduced the pain and distress of children undergoing many routine medical procedures, particularly the dread which builds up when these have to be repeated in the same child. It has also produced close to ideal conditions for the operator, and probably increased his efficiency by reducing the emotional strain which occurs when doing painful things to a frightened patient.